Solve for x: 2x – y = (3/4)x + 6
Answers
Answered by
1
Answer: x = 4(y + 6)/5.
Step-by-step explanation:
2x – y = (3/4)x + 6.
2x - (3/4)x = y + 6.
(8x -3x)/4 = y + 6.
5x/4 = y + 6.
5x = 4(y + 6).
5x = 4y + 24.
x = (4y + 24)/5.
Therefore, x = 4(y + 6)/5.
Answered by
4
Hey mate here is ur ans
As We given
2x-y=(3/4)x+6
4(2x-y)=3x+6
8x-8y=3x+6
8x-3x-8y=6
5x-8y=6
Now we can put the values to find x in this equation
so if y=1
5x-8=6
5x=14
x=14/5
Hope it helps u
![\beta e \beta rainly \beta e \beta rainly](https://tex.z-dn.net/?f=+%5Cbeta+e+%5Cbeta+rainly)
As We given
2x-y=(3/4)x+6
4(2x-y)=3x+6
8x-8y=3x+6
8x-3x-8y=6
5x-8y=6
Now we can put the values to find x in this equation
so if y=1
5x-8=6
5x=14
x=14/5
Hope it helps u
Similar questions
Math,
8 months ago
Math,
8 months ago
Social Sciences,
1 year ago
Math,
1 year ago
Physics,
1 year ago